Molecular targets of nickel and chromium in human and experimental systems. - Costa, M. (Scandinavian Journal of Work, Environment & Health, 1993)
Water-insoluble nickel compounds tend to be carcinogenic because they enter cells through phagocytosis. Highly water-soluble nickel salts, such as nickel chloride, do not enter cells well and thus are not carcinogenic in vivo. Carcinogenic nickel compounds produce selective damage to heterochromatic regions in Chinese hamster chromosomes, probably because of the high concentration of proteins and amino acids in this highly condensed genetically inactive chromatin region. Bivalent nickel ions are highly affinitive to amino acids as compared with deoxyribonucleic acid (DNA). The interaction with proteins is believed to cause this effect. In addition, when nickel binds to proteins, it can be oxidized, and DNA protein damage ensues. A new method detects DNA-protein cross-links induced by various agents, such as nickel, chromium and cis-platinum. It has demonstrated an increase in DNA-protein cross-links in cultured cells from animals treated with chromate and welders exposed to welding fumes.